2022
DOI: 10.1111/hex.13431
|View full text |Cite
|
Sign up to set email alerts
|

A self‐portrait: Design opportunities for a tool that supports children's involvement in brain‐related health care

Abstract: Introduction Paediatric patients with disorders that involve brain functioning are particularly vulnerable with respect to including them in shared decision‐making. Current tools are mostly paper or digital patient information. We lay the groundwork for improving engagement with a concept that we coined ‘the Self‐Portrait’. The main goals were to identify (1) obstacles and (2) design parameters that enable patient participation. Methods A research‐through‐design approach was utilized in nine patients with brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This includes Heerings et al's 42 adaptation of experience‐based codesign to involve people with independent living experiences—people with ID, serious mental illness and older people—in a participatory quality improvement initiative. Hudon et al's 35 adaption of patient‐reported outcome measures, a primary tool in the philosophy of patient‐centred care so that the administration of the tool gained sensitivity without compromising its psychometric properties, and Meulendijks et al 41 move beyond the status quo of paper or digital booklets to the involvement of children with brain injury in care decisions by developing wonderfully innovative brain puzzles and avatars.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This includes Heerings et al's 42 adaptation of experience‐based codesign to involve people with independent living experiences—people with ID, serious mental illness and older people—in a participatory quality improvement initiative. Hudon et al's 35 adaption of patient‐reported outcome measures, a primary tool in the philosophy of patient‐centred care so that the administration of the tool gained sensitivity without compromising its psychometric properties, and Meulendijks et al 41 move beyond the status quo of paper or digital booklets to the involvement of children with brain injury in care decisions by developing wonderfully innovative brain puzzles and avatars.…”
mentioning
confidence: 99%
“…First, we consider who is in spaces for sharing decisions about research, services and policy in this special issue. There are papers with lead authors from seven countries: the United Kingdom, [22][23][24][25][26][27][28] Australia, [29][30][31][32][33] Canada, [34][35][36][37][38] the United States, 39,40 the Netherlands, 41,42 France 43 and Ecuador. 44 There are important examples involving people who experience homelessness, 22,23,34 people who have disabilities, 26,41,42 people who live in socioeconomically disadvantaged circumstances 35,37 and people who are migrants and/or from ethnic minority groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations